2007
DOI: 10.1111/j.1365-2427.2007.01859.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term climatic trends affect the temporal variability of macroinvertebrates in California ‘Mediterranean’ streams

Abstract: 1. Long-term studies in ecology are essential for understanding natural variability and in interpreting responses to disturbances and human perturbations. We assessed the longterm variability, stability and persistence of macroinvertebrate communities by analysing data from three regions in northern California with a mediterranean-climate. During the study period, precipitation either increased or decreased, and extreme drought events occurred in each region. 2. Temporal trends in precipitation resulted in shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 48 publications
1
67
0
Order By: Relevance
“…These small community changes, however, have been significantly related to comparing wet-with-wet and dry-with-dry years [21]. Wet years are dominated by species adapted to high flows, whereas dry years include a higher proportion of lentic species [85]. Inter-annual community changes can interact with seasonal changes, resulting in differential effects under varying times of onset and the duration of the wet and dry seasons.…”
Section: Macroinvertebrate Communitiesmentioning
confidence: 96%
“…These small community changes, however, have been significantly related to comparing wet-with-wet and dry-with-dry years [21]. Wet years are dominated by species adapted to high flows, whereas dry years include a higher proportion of lentic species [85]. Inter-annual community changes can interact with seasonal changes, resulting in differential effects under varying times of onset and the duration of the wet and dry seasons.…”
Section: Macroinvertebrate Communitiesmentioning
confidence: 96%
“…Climate plays an obvious role as a driver of hydrologic pattern, and variability in rainfall and temperature has major consequences for the disturbance regime and habitat template of aquatic ecosystems (Firth & Fisher, 1992;Heino et al, 2008). Furthermore, multiyear studies in streams have shown that climate-driven changes in hydrology may substantially affect the structure of aquatic macroinvertebrate communities (Bêche & Resh, 2007;Durance & Ormerod, 2007;Magalhães et al, 2007;Power et al, 2008), and projected reductions in river discharge are expected to result in the widespread loss of species (Xenopoulos & Lodge, 2006). Because of this sensitivity to flow regime, aquatic ecosystems and their communities are recognized as useful sentinels for a suite of climate and land-use changes that have the potential to alter hydrologic routing in both the terrestrial and aquatic sectors of a landscape (Williamson et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These changes greatly influence the timing of emergence, reproduction, growth and development of many aquatic macroinvertebrates and, in turn, influence the seasonal replacement of organisms [54]. Thus, among the numerous environmental conditions, discharge and water temperature are often considered the important factors that contribute to the marked seasonality in assemblage composition [7,24,25,27,55]. According to the theory "intermediate disturbances", the season variations in discharge and water temperature enhance species richness and maintain maximum species density.…”
Section: Discussionmentioning
confidence: 99%
“…In climate regions with relatively high seasonal environmental variability or complex climatic patterns, the macroinvertebrate fauna was always characterized by the stochastic, unstable community structure in aquatic systems; within these systems, organisms had fast growth and high colonization capacity, and showed strong temporal variation or seasonality [31,55]. For instance, the species richness and abundance were significantly higher during the dry season than during the wet season in tropical streams [22,58].…”
Section: Discussionmentioning
confidence: 99%